Polymorphisms of SLCO1B1 Gene in Sundanese Ethnic Population of Tuberculosis Patients in Indonesia - Prayudi Santoso; Henny Juliastuti; Heda Melinda Nataprawira; Arto Yuwono Soeroto; Bachti Alisjahbana; Rovina Ruslami; Josephine Debora; Yunia Sribudiani; Ani Melani Maskoen (Acta Medica Indonesiana)
Background: The blood level of rifampicin, one of the tuberculosis (TB) drugs, depends on the organic anion transporting polypeptide 1B1 (OATP1B1) in hepatocytes. This protein is encoded by the solute carrier organic anion 1B1 (SLCO1B1) gene. Its genetic variation has been reported to have an impact on clinical outcomes and drug efficacy. However, the polymorphism in the SLCO1B1 gene has not been examined in Indonesia yet. We aimed to identify the frequency of polymorphism in SLCO1B1 gene among pulmonary TB patients in Bandung, Indonesia. Methods: Cross-sectional study was conducted in West Java. 145 pulmonary TB patients who were treated with first-line drugs treatment (including rifampicin 450 mg daily) were analyzed for polymorphism in SLCO1B1 gene. Patients aged between 18–64 years old and mainly came from Sundanese ethnic group (92.4%). Genetic variants were detected using Polymerase Chain Reaction (PCR) and Sanger sequencing. Results: Polymorphism of c.463C>A(rs11045819) was not identified, while heterozygous and homozygous polymorphism of c.85-7793C>T(rs4149032) were identified in 74 (51.0%) and 56 (38.6%) patients, respectively. The minor allele frequency (MAF) of T (mutant) allele of c.85-7793C>T(rs4149032) was 64.13% (186/209), higher than in the general population, which the MAF of rs4149032 is 53.6% based on 1000 genome database. Conclusion: This study highlights the presence of different allele frequencies of polymorphisms within the population, which might affect treatment outcomes.